Neurological manifestations in patients with multisystem inflammatory syndrome in children (MIS-C) in the post-COVID-19 era - Wati, Dyah Kanya; Suparyatha, Ida Bagus Gede; Hartawan, I Nyoman Budi; Manggala, Arya Krisna; Artini, Ni Wayan Noni; Aurelya, Anira Rema (Indonesian Pediatric Society, 2025)
Background Multisystem inflammatory syndrome in children (MIS-C) is an emerging condition associated with the COVID-19 pandemic. It occurs in approximately 2-8% cases of COVID-19, sometimes leading to shock, multiorgan failure, and the need for intensive care. Neurological manifestations are uncommon and sometimes overlap with previous comorbidities. Objective To explore the neurological manifestations in critically ill children with MIS-C. Methods This cross-sectional study included children aged <18 years, diagnosed with MIS-C according to World Health Organization (WHO) criteria and admitted to the pediatric intensive care unit (PICU) at a tertiary hospital in Bali, Indonesia. Retrospective data were extracted from electronic medical records covering January 2022 to December 2023. Demographic characteristics, clinical manifestations, treatments, and outcomes were collected and analyzed using SPSS. Patient were grouped based on the presence or absence of neurological symptoms for comparison. Results There were 47 children diagnosed with MIS-C; 78.7% of them were critically ill and treated in our intensive care unit. Thirty-seven subjects were included in the study. The most common symptom was fever (83.8%). Neurological manifestations were found in 12 children (32.4%), most commonly decreased consciousness (58.3%), followed by seizures (25.0%), hemiparesis (8.3%), and behavioral changes (8.3%). When comparing subjects with vs. without neurological symptoms, those with neurological manifestations had higher proportions of invasive mechanical ventilation (58.3% vs. 36.0%, respectively), combined use of intravenous immunoglobulin and methylprednisolone (83.3% vs. 64.0%, respectively), and mortality (58.3% vs. 28.0%, respectively). Conclusion Neurological manifestations, particularly decreased consciousness, were common in critically ill MIS-C patients. These patients exhibited higher rates of invasive ventilation and mortality, emphasizing the need for early recognition and targeted management.